ANALISIS KASUS COC AKUPRESURE TITIK SI 1 DAN ST36 UNTUK MELANCARKAN ASI DI PMB HESTI TULANG BAWANG - Ike Supihat (LPPM STIKes Mitra Adiguna, 2023)
Lampung Province in 2018 was recorded to have an MMR of 148 per 100,000 KH. The MMR value has not reached the target set by the SDGs. Efforts to help accelerate the reduction of MMR that can be done is to carry out continuous care or Continuity of Care. This ongoing care starts with ANC, INC, PNC, BBL and KB. This report aims to analyze the implementation of midwifery care according to standards and can provide complementary care. This case study uses a case analysis method in the form of midwifery care to 3 patients as respondents. This report uses complementary acupressure care interventions at SI 1 and ST36 points to expedite ASI which is carried out on the first day of the puerperium by applying 30-40x clockwise pressure which is done twice a day for 4 days. The results of the case studies showed that most of the care had been given according to standards, and after acupressure at SI 1 and ST36 points, there was an increase in breast milk volume. It is hoped that all midwives can provide midwifery care in a sustainable and complementary manner.